KOMPOSISI JENIS INVASIVE ALIENS SPECIES (IAS) DI KEBUN RAYA BATURRADEN, JAWA TENGAH - Endah Sulistiyowati; Pudji Widodo; Eming Sudiana (Universitas Tidar, 2020)
Ecologically Invasive Aliens Species (IAS) poses a particular threat to the conservation area that is a biodiversity sanctuary, Baturraden Botanical Garden (KRB). The purpose of this research is to find out the composition of IAS in KRB. This method of research is a survey method with purposive random sampling. Observation and prosecution is done by dividing krb into 10 plots. Information on the introduction process as well as conservation strategy recommendations is obtained through library studies and interviews with resouce person. The data then analyzed using the Importance Value Index (INP). The results showed that the IAS introduction process began in 1952 through the utilization of Protected Forest (HL) and Limited Production Forest (HPT) in KRB; The vegetation community structure in the KRB is dominated by spikes (saplings), seedlings, trees and poles. There were 13 IAS species consisting of 9 families; Seedling and saplings Calliandra houstoniana var. calothyrsus (Meissner) Barneby and Agathis dammara (Lamb). Rich. while at Agathis dammara (Lamb) tree level. Rich. and Schima wallichii Choisy. potential as a special IAS in the KRB; Controlling can be done through mitigation, periodic maintenance and eradication. In situ and ex situ conservation strategy plans in KRB are the creation of forest pharmacy conservation villages. Keywords: Baturraden Botanical Garden , biodiversity, Invasive Aliens Spesies (IAS)